2021
DOI: 10.1007/s12144-021-02267-5
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19: Psychological distress and coping among university students in Ghana

Abstract: The advent of the coronavirus pandemic has impacted the psychological well-being of many people. This study examined the relationship between fear of COVID-19, psychological distress (depression, anxiety, and stress) and coping strategies adopted by undergraduate students in Ghana. A sample of 209 students were recruited to complete online surveys on fear of COVID-19, psychological distress and coping strategies between June and July 2020. Students scored between normal to mild levels of psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 53 publications
4
26
2
Order By: Relevance
“…Nevertheless, the mean values of DASS-21 scores recorded in the present study were higher than in studies conducted in Spain and Ghana, two months after the beginning of the pandemic [43,45]. The recorded level of fear of COVID-19 measured using the FCV-19S scale in the present study was also lower than in previous studies among university students [45][46][47]. In addition to the stated reason regarding the different time periods when studies were conducted, the reasons for such results can be found in the different number of infected people, deaths, and measures of total lockdown in different countries.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, the mean values of DASS-21 scores recorded in the present study were higher than in studies conducted in Spain and Ghana, two months after the beginning of the pandemic [43,45]. The recorded level of fear of COVID-19 measured using the FCV-19S scale in the present study was also lower than in previous studies among university students [45][46][47]. In addition to the stated reason regarding the different time periods when studies were conducted, the reasons for such results can be found in the different number of infected people, deaths, and measures of total lockdown in different countries.…”
Section: Discussioncontrasting
confidence: 95%
“…It must be emphasized that all of these studies were conducted early in the COVID-19 outbreak so that the results could be expected due to partial adaptation to the pandemic after a year and a half. Nevertheless, the mean values of DASS-21 scores recorded in the present study were higher than in studies conducted in Spain and Ghana, two months after the beginning of the pandemic [43,45]. The recorded level of fear of COVID-19 measured using the FCV-19S scale in the present study was also lower than in previous studies among university students [45][46][47].…”
Section: Discussioncontrasting
confidence: 91%
“…[ 40 ]. The low sense of control induced by pandemic fear may also be related to emotion-focused coping behaviors [ 41 ]. From this standpoint, we argue that pandemic fear will increase emotion-focused coping but hinder problem-focused coping.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Around the world, COVID-19 has been found to have an enormous negative impact on various well-being indicators including mental health [8][9][10][11][12][13]. For instance, fear associated with COVID-19 propels people to be anxious in protecting themselves and their loved ones, which can lead to social isolation, fear, and panic [14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, fear associated with COVID-19 propels people to be anxious in protecting themselves and their loved ones, which can lead to social isolation, fear, and panic [14]. A recent study by Oti-Boadi et al [11] found that Ghanaian students experienced normal to mild levels of psychological distress but reported above average scores on fear of coronavirus. In addition, a longitudinal study among youth in the United Kingdom showed an increase in mental health challenges (including increased use of maladaptive coping strategies and decreased physical activity) during the COVID-19 outbreak, especially among females and those with preexisting conditions, among other findings [13].…”
Section: Introductionmentioning
confidence: 99%